Effects of residence time on the characteristics of PAN-based fibers and its fabrication through solvent-free coagulation process - Ismail, Ahmad Fauzi; Rahman, M. A.; Mustafa, A.; Ng, B. C.; Hasbullah, Hasrinah; Rahaman, M. S. A.; Abdullah, M. S. (2006)
The paper reports the fabrication and characterizations of PAN fibers fabricated using residence time in the range of 2 – 5 s in the solvent free coagulation process. The PAN fibers were characterized using SEM, FTIR-ATR and tensile testing machine. The SEM photographs revealed that the cross-section of PAN fiber, for all sample was free from large void. A residence time of 3 s was found to be the most suitable residence time for fabricating the PAN fibers in the solvent-free coagulation bath. FTIR-ATR data suggested that the PAN fibers possess better molecular orientation and exhibited the highest Young's modulus of 2.55 GPa.